THE EFFECT OF PROPORTION OF RED BEAN FLOUR AND SOYBEAN ON ACCEPTABILITY AND NUTRITIONAL CONTENT OF SNACK BARS AS A HIGH PROTEIN DIET SNACK - Rahmawati, Dinda Ayu (Jurnal Gizi dan Kesehatan Nusantara, 2023)
Snack bars are snacks in the form of bars made from cereals or nuts. Snack bars are a type of healthy snack that contains high protein nutrients. The purpose of this study was to determine the effect of the proportions of red bean flour and soybean on acceptability (color, aroma, taste, and texture) and nutritional content (energy, carbohydrates, protein, and fat) in the best snack bar formula as a high protein diet. This study used a true experimental study with a completely randomized design with 3 treatments proportion red bean flour and soybean (25% : 75%, 50% : 50%, 75% : 25%) by weight of the basic ingredients of oats in the manufacture of snack bars. The panelists in this study were semi-trained panelists consisting of 35 people. Data acceptance results were analyzed using non-parametric statistics, namely Kruskal Wallis. The results of acceptance which have a significant effect, further analysis is carried out with the Mann Whitney test to find out the best results. The proportion of red bean flour and soybean has an effect on the acceptability of aroma and texture but does not affect the color and taste of the snack bar. The best snack bar formula is with a proportion of 50% red bean flour and 50% soy beans. The test results for the best formula nutritional content per 100 grams of snack bar were energy of 365.67 kcal, carbohydrates 28.15%, protein 20.10%, and fat 19.19%.